Skill profiles of training occupations and occupational segmentation of vocational education and training in Germany - Koneberg, Filiz [Verfasser]; Rohrbach-Schmidt, Daniela [Verfasser]; Friedrich, Anett [Verfasser] (My University, 2025)
Vocational education and training (VET) is crucial for labour market integration and ensuring a skilled workforce. However, VET systems, particularly in countries like Germany and Switzerland, offer heterogeneous training occupations with different labour market returns. This study examines occupational segmentation within VET, applying labour market segmentation theories to identify structural differences in skill profiles, training commitment, gratification and social access based on school-leaving certificates. Utilising the German VET system as a case study, we analyse data from 338 dual and school-based training occupations. We employ latent profile analysis to classify training occupations into skill profiles according to their firm-specific and occupation-specific skills, as well as their cognitive requirement level. The analyses reveal four distinct skill profiles that are systematically associated with training commitment, gratifications and social access based on school-leaving certificates. The results suggest that VET is stratified into occupational training segments, offering training at varying skill levels. These segments exhibit unequal training conditions, with some providing significantly higher commitment or higher gratifications. This research provides a more nuanced understanding of VET segmentation than the distinction into dual and school-based trainings, offering valuable insights for political actors and institutions involved in VET, as well as training firms and vocational schools.“ (authors‘ abstract; BIBB-Doku)
Keywords: S 6 Berufsbereiche; G 1.2.3.2 Anforderungen & Bedarfe; 370; Ausbildungsberuf; Berufsprofil; Anforderungsprofil; Qualifikationsniveau; Arbeitsmarktsegmentation; Segmentationstheorie